Digital Economy - Borovitskiy P. I. (Law, Economics and Management, 2020)
the digital economy is a new step to the informatization of human society. The Internet and other digital technologies form the necessary base for future development. Cryptocurrency is a new solution of an old problem. It’s been considered a place of cryptocurrency in the world digital economy. There is the range of problems and perspectives of Russian integration into digitalization.
Keywords: информационные технологии; Россия; интернет; цифровая экономика; бизнес; information technologies; Russia; business; digital economy; цифровая валюта; the Internet; digital currency